Novel approaches to determine contractile function of the isolated adult zebrafish ventricular cardiac myocyte. (4th April 2014) - Dvornikov, Alexey V.; Dewan, Sukriti; Alekhina, Olga V.; Pickett, F. Bryan; de Tombe, Pieter P.
<x xml:space="preserve">Abstract</x> Key points The zebrafish is emerging as an attractive cost‐effective model for the study of structure–function relationships. However, cardiac contractile function in the zebrafish remains to be investigated. We applied novel approaches used to study contractile function at the cellular level in mammalian models to zebrafish. We found that contractile force regulation in the adult zebrafish shares many similarities with that in the mammalian myocardium as previously determined by others and ourselves, indicating that the zebrafish is an appropriate model system for the study of cardiac contractile biology. Abstract The zebrafish (Danio rerio) has been used extensively in cardiovascular biology, but mainly in the study of heart development. The relative ease of its genetic manipulation may indicate the suitability of this species as a cost‐effective model system for the study of cardiac contractile biology. However, whether the zebrafish heart is an appropriate model system for investigations pertaining to mammalian cardiac contractile structure–function relationships remains to be resolved. Myocytes were isolated from adult zebrafish hearts by enzymatic digestion, attached to carbon rods, and twitch force and intracellular Ca2+ were measured. We observed the modulation of twitch force, but not of intracellular Ca2+, by both extracellular [Ca2+] and sarcomere length. In permeabilized cells/myofibrils, we found robust myofilament length‐dependent activation. Moreover, modulation of myofilament activation–relaxation and force redevelopment kinetics by varied Ca2+ activation levels resembled that found previously in mammalian myofilaments. We conclude that the zebrafish is a valid model system for the study of cardiac contractile structure–function relationships.